2017
DOI: 10.1016/j.ijfoodmicro.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

S. Typhimurium virulence changes caused by exposure to different non-thermal preservation treatments using C. elegans

Abstract: The aims of this research study were: (i) to postulate Caenorhabditis elegans (C. elegans) as a useful organism to describe infection by Salmonella enterica serovar Typhimurium (S. Typhimurium), and (ii) to evaluate changes in virulence of S. Typhimurium when subjected repetitively to different antimicrobial treatments. Specifically, cauliflower by-product infusion, High Hydrostatic Pressure (HHP), and Pulsed Electric Fields (PEF). This study was carried out by feeding C. elegans with different microbial popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…All inferential processes agree with the conclusions in Sanz‐Puig et al. (2017) that the cauliflower by‐product infusion can be an alternative preservation treatment. This fact evidences the robustness (regardless of the h0false(tfalse) specification) of the Cox model in estimating covariate effects.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All inferential processes agree with the conclusions in Sanz‐Puig et al. (2017) that the cauliflower by‐product infusion can be an alternative preservation treatment. This fact evidences the robustness (regardless of the h0false(tfalse) specification) of the Cox model in estimating covariate effects.…”
Section: Discussionsupporting
confidence: 87%
“…ST non‐treated ( ST0 ), ST treated once ( ST1 ), and ST treated three times ( ST3 ) was the source of nutrition of 250 synchronized young adult nematodes kept in identical environmental conditions throughout their lifespan (approximately three weeks at the most). Virulence for each worm was defined in terms of their survival time (see Sanz‐Puig et al., 2017, for more details about the validation and special conditions of the study). Most of the data were fully observed.…”
Section: An Experiments On Microbial Virulencementioning
confidence: 99%
“…It has also been found that many vegetables in the Cruciferae family have antimicrobial properties against several microorganisms of clinical importance. The in vitro antibacterial effect of Brassica oleracea products on several foodborne pathogens was evidenced by Brandi et al (2006) and Sanz-Puig et al (2017), between others. Some of the antimicrobial properties of these plant extracts are associated with antioxidant compounds such as polyphenols (Sanz-Puig et al, 2015b;Marchese et al, 2016;Bakari et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…Caenorhabditis elegans has been used very frequently as a model of pathogenesis, and in particular for infection by pathogenic microorganisms ( Balla and Troemel, 2013 ; Curt et al, 2014 ). In this sense, there are published studies in which the antimicrobial activity of a compound has been determined based on a higher survival of infected C. elegans when exposed to the antimicrobial compounds when compared with infected control nematodes (non-exposed to the antimicrobial compound) ( Sanz-Puig et al, 2017 ; Ibáñez-Peinado et al, 2020 ; Palacios-Gorba et al, 2020 ). In the present study, an independent set of experiments was specifically designed to study the Spirulina (treated and untreated by CP) antimicrobial activity against Salmonella enterica serovar Typhimurium when C. elegans worms were infected.…”
Section: Resultsmentioning
confidence: 99%